2016
DOI: 10.1039/c5cy01470k
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodeoxygenation of karanja oil over supported nickel catalysts: influence of support and nickel loading

Abstract: Conversion of oxygenates increased in the order 25NiSi < 25NiAl ≤ 25NiZSM. The HDO route was dominant over (≥20 wt%) Ni/γ-Al2O3. The optimal conditions for the HDO route were 653 K and 25NiAl at 35 bar H2. The properties of green diesel were comparable with light diesel oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…They observed that the best conversion (100%) and diesel selectivity (97%) were achieved with the lab-made NiMo/Al-SBA-15 (zeolite SBA-15 enriched with Al), which has the highest surface area and the largest porosity [ 46 ]. The correlation between support surface area and catalyst activity has been observed by several authors [ 47 , 48 , 49 , 50 ]. The acidity of the support is another parameter that can affect the deoxygenation reaction.…”
Section: Catalytic Deoxygenation (Do) Processmentioning
confidence: 68%
“…They observed that the best conversion (100%) and diesel selectivity (97%) were achieved with the lab-made NiMo/Al-SBA-15 (zeolite SBA-15 enriched with Al), which has the highest surface area and the largest porosity [ 46 ]. The correlation between support surface area and catalyst activity has been observed by several authors [ 47 , 48 , 49 , 50 ]. The acidity of the support is another parameter that can affect the deoxygenation reaction.…”
Section: Catalytic Deoxygenation (Do) Processmentioning
confidence: 68%
“…Alumina is a ubiquitous supporting material for a variety of catalytic reactions, due to its high specic surface area (which improves metal dispersion) and high thermal stability under reaction conditions. [29][30][31][32][33][34][35][36] Moreover, as it is mildly acidic, a property that is considered benecial in catalysts used for the deoxygenation of triglycerides, it has been used extensively in catalytic systems tested in the SDO process. An excellent work was provided by Gousi et al, 36 which screened Ni catalysts with loading in the range of 0-100 wt%, in a semi-batch reactor at 310 C, 40 bar and volume of oil (mL)/mass of catalyst (g) ratio equal to 100, and observed that both the conversion of sunower oil and the yield of hydrocarbons maximize at Ni about 60 wt%.…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] Although jatropha oil can be converted to biodiesel via transesterification or esterification, this kind of biodiesel is not widely used for the high oxygen content bringing about a low heat value, high viscosity, low volatility, and instability. [20][21][22] Therefore, substantial research has been carried out to remove the oxygen atom and obtain hydrocarbons, which could provide an outstanding performance comparing to conventional biodiesel. [23][24][25][26] The deoxygenation of jatropha oil had been researched with diverse catalysts such as Pt-, Pd-, Ru-, Ni-, Mo-, and Co-based catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Jatropha oil is mainly composed of triglycerides including a small amount of free fatty acids . Although jatropha oil can be converted to biodiesel via transesterification or esterification, this kind of biodiesel is not widely used for the high oxygen content bringing about a low heat value, high viscosity, low volatility, and instability . Therefore, substantial research has been carried out to remove the oxygen atom and obtain hydrocarbons, which could provide an outstanding performance comparing to conventional biodiesel …”
Section: Introductionmentioning
confidence: 99%